2003
DOI: 10.1021/ja028982q
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Janus Micelles with Polystyrene and Poly(methacrylic acid) Hemispheres

Abstract: We describe the synthesis and the solution properties of Janus micelles containing a polybutadiene (PB) core and a compartmentalized corona consisting of a poly(methacrylic acid) (PMAA) and a polystyrene (PS) hemisphere. The Janus micelles were obtained via cross-linking the middle block of a microphase-separated PS-block-PB-block-PMMA triblock copolymer in the bulk state, followed by alkaline hydrolysis of the poly(methyl methacrylate) (PMMA) ester groups. Results of fluorescence correlation spectroscopy, fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
318
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 350 publications
(334 citation statements)
references
References 12 publications
6
318
0
10
Order By: Relevance
“…[ 262 ] Cylinders, sheets, and ribbons Poly(tert-butoxystyrene)-bpoly(butadiene)-b-poly(tertbutyl methacrylate)…”
Section: Reviewmentioning
confidence: 99%
“…[ 262 ] Cylinders, sheets, and ribbons Poly(tert-butoxystyrene)-bpoly(butadiene)-b-poly(tertbutyl methacrylate)…”
Section: Reviewmentioning
confidence: 99%
“…Müller and coworkers prepared disc-like polymer Janus particles from assem-bled films of polystyrene-block-poly(butadiene)-block-PMMA triblock copolymer (SBM) [42], selective crosslinking of the poly(butadiene) block, and dissolution via sonication, and then assembled them into supracolloidal Janus micelles. They revisited this in another paper and described the hydrolysis of the PMMA into poly(methacrylic acid) [43]. Again, assembly into supracolloidal micelles was driven by the hydrophobic effect.…”
Section: Self-assembly Of Amphiphilic Particles Driven By the Hydrophmentioning
confidence: 99%
“…Although the aggregate is still in thermodynamic equilibrium, the degree of stretching is different when polymers form aggregates of different morphologies. 40 For example, Zhang and Eisenberg 2 showed that spheres, rods, and vesicles were formed from PS 200 -b-PAA 21 , PS 200 -b-PAA 15 , and PS 200 -b-PAA 8 copolymers, respectively, in dimethylformamide (DMF)/water solutions. The degree of PS stretching in these three types of aggregates was 1.41, 1.26, and 0.99, respectively.…”
Section: Copolymer Composition and Concentrationmentioning
confidence: 99%